Below-ground abiotic and biotic heterogeneity shapes above-ground infection outcomes and spatial divergence in a host-parasite interaction - Tack, Ayco J M (The New phytologist, 2015)
© 2015 The Authors. New Phytologist © 2015 New Phytologist Trust.